Reducing the Sugar and pH of the Grape (Vitis vinifera L. cvs. ‘Grenache’ and ‘Tempranillo’) Through a Single Shoot Trimming - Martínez de Toda, F.; Sancha, J.C.; Balda, P. (South African Journal of Enology and Viticulture, 2013)
Many vineyards all over the world can easily produce high potential alcohol levels, but the importance of the sugar content in berries has been changing over the past few years. The objective of this work was to reduce the sugar and pH of the grapes, delay berry ripening by decreasing the ratio between the leaf area and yield, perform an intense trimming treatment after berry set and establish the consequences for grapevine productivity in the following year. Severe shoot trimming was done over a three-year period (2010 to 2012). Phenological, vegetative and productive parameters were examined. The date of véraison was delayed by about 20 days. On the same harvesting date, the trim treatment had lower soluble solids (12% to 15 % reduction), lower pH (0.1 to 0.3) and a lower total anthocyanin content (10% reduction). The trim effect was also reflected in berry weight; as a consequence, bunch size and yield were also reduced by around 10%. If the trim treatment does not reduce the leaf area to fruit ratio below 0.50 m2/kg, there is no negative impact on vine capacity in the next year.